2004
DOI: 10.1098/rspb.2004.2856
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining multiple separate food sources: behavioural intelligence in the Physarum plasmodium

Abstract: To evaluate performance in a complex survival task, we studied the morphology of the Physarum plasmodium transportation network when presented with multiple separate food sources. The plasmodium comprises a network of tubular elements through which chemical nutrient, intracellular signals and the viscous body are transported and circulated. When three separate food sources were presented, located at the vertices of a triangle, the tubular network connected them via a short pathway, which was often analogous to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
153
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(157 citation statements)
references
References 11 publications
(19 reference statements)
2
153
0
2
Order By: Relevance
“…Secondly, how does the organism realize this smartness? Even unicellular organisms can demonstrate a greater capacity than initially thought for processing information, for example by solving a maze (Nakagaki et al, 2000a;Nakagaki, 2001; Nakagaki et al, 2004a;Nakagaki et al, 2004b). Here we provide an answer to the question of how the amoeboid true slime mold, Physarum polycephalum, realized this capacity.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Secondly, how does the organism realize this smartness? Even unicellular organisms can demonstrate a greater capacity than initially thought for processing information, for example by solving a maze (Nakagaki et al, 2000a;Nakagaki, 2001; Nakagaki et al, 2004a;Nakagaki et al, 2004b). Here we provide an answer to the question of how the amoeboid true slime mold, Physarum polycephalum, realized this capacity.…”
mentioning
confidence: 82%
“…Thus, the geometry of the tube network is related to the transport of materials and information within the organism. Since the tubes disassemble and reassemble within a period of a few hours in response to external conditions, this system is very useful for studying the function and dynamics of natural adaptive networks (Nakagaki et al, 2004a;Nakagaki et al, 2004b).…”
mentioning
confidence: 99%
“…Introduction.-The plasmodium of Physarum polycephalum is an amoebalike organism with a body made up of a tubular network through which nutrients, signals, and body mass are transported. Studies of this organism have shown that it is able to determine the shortest path through a maze as well as ''solve'' other geometric puzzles [1][2][3]. In a maze, a starved organism forms a tube that connects food sources (FS) placed at the two exits of the maze via the shortest path, while nearly the entire protoplasm of the amoeba gathers over the two FS.…”
mentioning
confidence: 99%
“…Further studies are needed to establish whether this is the result of random errors in the information processing cascade that occur with low probability and thus, after a period of exploration, cause the escape, or whether a more sophisticated mechanism gives rise to the approach of the repellent. Studies with multiple attractants also indicate a graceful response of the plasmodium [24].…”
Section: Self-repair and Robust Behaviourmentioning
confidence: 99%
“…Nakagaki and coworkers, for example, showed that the plasmodium can find the shortest path in a maze [23] and that it can solve small instances of optimisation problems [24]. Aono recently constructed a novel neural network system driven by a plasmodium [25].…”
Section: Distributed Information Processingmentioning
confidence: 99%